NAVIGABILITY IN THE PAST. THE VOUGA RIVER AS A CASE STUDY IN THE ROMAN PERIOD: The case study of the Vouga River in Roman times. - Marques, Joana (Riparia, 2026)
This paper examines the feasibility of navigating the Vouga River during the Classical period, from its mouth to the vicinity of the archaeological site of Castro do Banho, in São Pedro do Sul (Viseu, Portugal). The study draws on landscape archaeology, historical sources, and hydrographic analyses conducted in a GIS environment. To complement this approach, the morphology of the drainage basin and rainfall data were analysed, and experimental calculations were carried out to estimate river depth and width for the period under minimum and maximum conditions. The work applies a recently proposed method, enabling a more detailed assessment in this type of case study